2000
DOI: 10.1046/j.1439-037x.2000.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microclimatic Parameters at Different Sowing Dates on Capsule Production of Sesame (Sesamum indicum L.) in a Tropical Humid Region

Abstract: An experiment was conducted during the summer seasons of 1993 and 1994 on sesame (Sesamum indicum L.) to study the effect of certain meteorological parameters on the capsule production efficiency of the main stem and branches of sesame cultivars at different sowing dates in alluvial (Entisol) soil of the tropical humid region in West Bengal, India. The highest capsule production by the main stem and the first, second and third primary branches in accrocentric order was observed for the crop sown on 19 February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
4
1
Order By: Relevance
“…However, Patil et al (1992) reported that increased number of capsule plant -1 with delaying sowing might be due to difference in genetic makeup and climatic conditions. This finding was in agreement with the result obtained by Nath et al (2000) and Rai et al (1999).…”
Section: Effect Of Dates Of Sowing and Cultivars On Yield Components supporting
confidence: 94%
“…However, Patil et al (1992) reported that increased number of capsule plant -1 with delaying sowing might be due to difference in genetic makeup and climatic conditions. This finding was in agreement with the result obtained by Nath et al (2000) and Rai et al (1999).…”
Section: Effect Of Dates Of Sowing and Cultivars On Yield Components supporting
confidence: 94%
“…Sesame sown on 15 March produced the highest seed yield (760.1 kg ha -1 ), which was 3.4, 3.8 and 18.3% greater over 1 March, 1 April and 15 February, respectively. The finding contradicted Nath et al, (1997) [6] , where maximum seed yield of sesame varieties was obtained with sowing on 19 February compared to early (10 February) and delayed sowings (1 March to 28 April) at Kalyani, Nadia, West Bengal. Among three varieties, Rama recorded the highest seed yield (731.8 kg ha -1 ) due to significant improvement in yield components, stover yield (2390.0 kg ha -1 ) and oil content (38.4%).…”
Section: Resultscontrasting
confidence: 66%
“…Periods of high temperature above 40°C during flowering reduce number of capsule and seed development. It requires from 600 to 1000 mm amount of water (Nath et al, 2000).…”
Section: Introductionmentioning
confidence: 99%